2017
DOI: 10.5812/ircmj.55039
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cupping Therapy on Non-specific Neck Pain: A Systematic Review and Meta-Analysis

Abstract: Context: Neck pain is a very common symptom. Several clinical trial studies were conducted to evaluate the effects of cupping therapy on neck pain. The objective of this study was to assess the evidence for the effectiveness of cupping therapy as an intervention to conservative management of neck pain.Evidence Acquisition: We performed a systematic search in PubMed, Ovid, MEDLINE, CINAHL, EMBASE, Cochrane Library, web of science, and Iranian medical databases through March 2017 without time restrictions. All c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, there is no documented study in this area. Due to the limitations and side effects of the drugs used in the management of AUB on one hand, and the simplicity, speed of impact, lack of severe side effects, not interacting with other therapies of dry cupping on the other hand, it is necessary to conduct a study to demonstrate the effectiveness of this treatment as a novel method (9)(10)(11)(12). The aim of this study was to evaluate the usefulness of dry cupping on excessive menstrual blood loss in menorrhagia, with a well-validated menstrual pictogram compared to medroxyprogesterone acetate.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no documented study in this area. Due to the limitations and side effects of the drugs used in the management of AUB on one hand, and the simplicity, speed of impact, lack of severe side effects, not interacting with other therapies of dry cupping on the other hand, it is necessary to conduct a study to demonstrate the effectiveness of this treatment as a novel method (9)(10)(11)(12). The aim of this study was to evaluate the usefulness of dry cupping on excessive menstrual blood loss in menorrhagia, with a well-validated menstrual pictogram compared to medroxyprogesterone acetate.…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicates and screening the titles and abstracts, there were 19 potentially eligible studies. We finally included 14 studies ( 22–35 ) after assessing for eligibility including five types of pain-related conditions. The study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies ( 23 , 26 , 28 , 30 , 31 ) contained less than ten original studies, while twelve (85.7%) studies ( 23–30 , 32–35 ) had a combined total sample of over 500 participants. The majority of studies, eight (57.1%) in total ( 23 , 26 , 29–31 , 33–35 ), were conducted in China, followed by two ( 25 , 28 ) in Korea, and one each in Germany ( 24 ), Brazil ( 27 ), Australia ( 32 ), and Iran ( 22 ). The included studies investigated various conditions, including low back pain ( n = 4), neck pain ( n = 3), knee osteoarthritis ( n = 2), chronic back pain ( n = 1), migraine ( n = 1), chronic pain ( n = 1), pain-related conditions ( n = 1), musculoskeletal pain ( n = 1), and herpes zoster ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wet cupping therapy can generally be described as a technique that uses in several medical conditions. The most important evidence for therapeutic benefit of cupping therapy is relief pain ( 7 ). Cupping therapy is effective to management of Iron overloud, dyspnea, and acne ( 6 ).…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%